Mutations and polymorphism in bottlenose dolphin (Tursiops truncatus, Montagu 1821) albumin gene: First identification of mutations responsible for inherited bisalbuminemia. (October 2017) - Gili, Claudia; Bonsembiante, Federico; Beffagna, Giorgia; Mazzariol, Sandro; Gelain, Maria Elena
Abstract: Hereditary bisalbuminemia is an asymptomatic and heterozygous condition in a range of species characterized by the presence of two serum albumin fractions with different electrophoretic mobility resulting in a bicuspid pattern on serum electrophoresis. Bisalbuminemia has been diagnosed by electrophoresis in two bottlenose dolphin ( Tursiops truncatus ) families, but causative mutations and the inheritance pattern have not been identified. The aims of this work are: to investigate polymorphisms of the bottlenose dolphin albumin gene and to identify mutations causative of bisalbuminemia; to identify the inheritance pattern in two bottlenose dolphin families. Coding regions of the albumin gene were screened for mutations in 15 bottlenose dolphins kept under human care from two distinct families. Eighteen albumin mutations (three synonymous and 15 non-synonymous) were identified. Two non-synonymous variations co-segregated with bisalbuminemic phenotype: p.Phe146Leu in exon 4 and p.Tyr163His in exon 5. The amino acid change in exon 5 was associated with the secondary and/or tertiary structure variation of the protein and has been reported as causative of bisalbuminemia in humans. Pedigree analysis of the dolphin families showed an autosomal codominant inheritance pattern. In this work, the mutations potentially responsible for bisalbuminemia were identified and confirmed the autosomal codominant trait in bottlenose dolphins. Highlights: A significant polymorphism in the bottlenose dolphin albumin gene were identified. Two mutations associated with bisalbuminemia were identified for the first time. An autosomal codominant inheritance pattern for bisalbuminemia in Bottlenose dolphins was demonstrated.